2013
DOI: 10.1038/npp.2013.292
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid Receptor Activation Prevents the Effects of Chronic Mild Stress on Emotional Learning and LTP in a Rat Model of Depression

Abstract: Most psychiatric disorders are characterized by emotional memory or learning disturbances. Chronic mild stress (CMS) is a common animal model for stress-induced depression. Here we examined whether 3 days of treatment using the CB1/2 receptor agonist WIN55,212-2 could ameliorate the effects of CMS on emotional learning (ie, conditioned avoidance and extinction), long-term potentiation (LTP) in the hippocampal-accumbens pathway, and depression-like symptoms (ie, coping with stress behavior, anhedonia, and weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
58
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 92 publications
(144 reference statements)
3
58
0
Order By: Relevance
“…Animal studies show that cannabinoid agonists promote antidepressant-and anxiolytic-like responses (Bortolato et al 2007;McLaughlin et al 2007;GanonElazar and Akirav 2012;Abush and Akirav 2013;Segev et al 2013).…”
mentioning
confidence: 99%
“…Animal studies show that cannabinoid agonists promote antidepressant-and anxiolytic-like responses (Bortolato et al 2007;McLaughlin et al 2007;GanonElazar and Akirav 2012;Abush and Akirav 2013;Segev et al 2013).…”
mentioning
confidence: 99%
“…CMS significantly modified physiological and behavioral reactions, as observed by the impairment in avoidance extinction and LTP in the hippocampal-accumbens pathway, and the alterations in depressionlike symptoms, such as coping with stress behavior, weight gain, and sucrose consumption [35]. Exposure to CMS produces downregulation of the cannabinoid 1 (CB1) receptor in the hippocampus of male rats.…”
Section: Literaturementioning
confidence: 99%
“…Liu et al [34] demonstrated that a rat model of CUS induced a cognitive impairment in spatial memory and the Morris water maze test and a hippocampal LTP impairment accompanied by microglial activation and attenuated phosphorylation of glutamate receptor 1 (GluR1 or GluA1). Blockade of microglial activation by chronic treatment with minocycline before CUS prevented CUS-induced impairments of both spatial memory and LTP induction as well as increased phosphorylation of GluR1.CMS significantly modified physiological and behavioral reactions, as observed by the impairment in avoidance extinction and LTP in the hippocampal-accumbens pathway, and the alterations in depressionlike symptoms, such as coping with stress behavior, weight gain, and sucrose consumption [35]. Exposure to CMS produces downregulation of the cannabinoid 1 (CB1) receptor in the hippocampus of male rats.…”
mentioning
confidence: 95%
“…We found that the CB1/2 receptor agonist WIN55,212-2 (WIN) prevented the effects of stress on learning and plasticity, as well as the behavioral and neuroendocrine outcomes of stress (Abush and Akirav, 2013;Ganon-Elazar and Akirav, 2009, 2013. Specifically, systemic administration of WIN or the GR antagonist RU-38486 (RU) prevented the impairment in extinction and NAc plasticity induced by exposure to chronic mild stress (Segev et al, 2014), and intra-BLA WIN or RU administered before stress exposure prevented the stress-induced enhancement of memory consolidation for reduction in reward magnitude .…”
Section: Introductionmentioning
confidence: 99%
“…Stress and glucocorticoids can trigger eCB synthesis and CB1 receptors signaling to constrain HPA axis activity under acute conditions (Hill et al, 2011;Rademacher et al, 2008;Steiner and Wotjak, 2008). Blocking BLA GRs prevented the effects of stress on a variety of memory tasks (Maroun and Akirav, 2007;Roozendaal et al, 2002;Segev et al, 2012Segev et al, , 2014.…”
Section: Introductionmentioning
confidence: 99%